Technological innovation and organizational resilience: A dual challenge for entrepreneurial enterprises - You, Yue; Fatmawati, Latada (Global Academic Excellence (M) Sdn. Bhd., 2025)
This study explores the interaction between technological innovation, organizational resilience, organizational culture building, and innovation-driven development in Chinese entrepreneurial enterprises. Based on Innovation Systems Theory, a quantitative approach was employed using survey data from 207 entrepreneurial firms in China. Reliability, validity, correlation, and regression analyses were conducted via SPSS 27 and AMOS 26. Results show that both technological innovation and organizational resilience significantly promote innovation-driven development, with technological innovation having a stronger impact. Organizational resilience positively influences technological innovation, while the reverse effect is not significant. Organizational culture building did not demonstrate a moderating effect in this context. The study enriches existing theory by clarifying the asymmetrical relationship between innovation and resilience. It also offers practical guidance for entrepreneurial firms to strengthen resilience while fostering innovation for high-quality development.